Brasil y la República Federal de Alemania : ¿Un modelo para las relaciones entre el primer y tercer mundo? - Grabendorff, Wolf (Estudios Internacionales, 1982)
Brazil is the Third World country with which the Federal Republic of Germany has the closest relations. In the discussion that has taken place within the Federal Republic about the improvement of relations within the North-South configuration, German-Brazilian relations can be considered as a model for the problems and perspectives of the bilateral relationship between a industrialized country and a Third World country that is on the threshold of industrialization. The purpose of this work is to examine the extent and importance, on both sides, of bilateral relations in the fields of economy, culture, politics, and development policies, as well as those factors that have become evident in the difficulties encountered in the current sphere of cooperation.